Ethyl 5-(4-aminophenyl)isoxazole-3-carboxylate - Jun-Tao Zhao; Jing-Jing Qi; You-Jun Zhou; Jia-Guo Lv; Ju Zhu (Acta Crystallographica Section E, 2012)
The asymmetric unit of the title compound, C12H12N2O3, contains two molecules in which the benzene and isoxazole rings are almost coplanar, the dihedral angles between their mean planes being 1.76 (9) and 5.85 (8)°. The two molecules interact with each other via N—H...N and N—H...O hydrogen bonds, which link the molecules into layers parallel to the ac plane. The layers stack in a parallel mode with an interlayer distance of 3.36 (7) Å.